THE RELATIONSHIP BETWEEN KNOWLEDGE, INFORMATION SOURCES, FAMILY SUPPORT AND IMPLEMENTATION OF PROVIDER-INITIATED TESTING AND COUNSELING IN PREGNANT WOMAN - Ciptiasrini, Uci (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2020)
The discovery of cases of HIV and AIDS at the age of under four years old in Indonesia indicates that there is still HIV transmission from mother to child. This study aims to identify the relationship between knowledge, information sources, family support, and the implementation of Provider-Initiated Testing and Counseling (PITC) examinations in pregnant women. This research was analytic descriptive with a cross-sectional approach conducted in August 2018, with 85 respondents selected by accidental sampling. The population in this study were all pregnant women who visited the community health center. Data was collected by giving questionnaires directly to respondents. Relationships between variables were tested with chi-square analysis. The results showed that 36 (62.1%) respondents have good behavior and good knowledge, and the chi-square test results obtained p-value=0.025. Thirty (68.2%) respondents have good behavior and have access to information sources and p-value=0.007. Thirty-three (67.3%) respondents have good behavior and have family support with the p-value=0.004. It can be concluded that there is a relationship between knowledge, information sources, family support, and the implementation of the PITC examination of pregnant women.